Comparison of Maylard and Cherney incisions' outcomes in hysterectomy surgery for benign indications: a double-blind randomized controlled trial - Maryam Vaezi; Roghayeh Zarei; Hosein Azizi (European Journal of Medical Research)
Abstract Objectives Choosing the incision for surgery depends on a variety of factors, including the surgeon's preference, patient preference, surgical indications, the patient's systemic issues, previous surgical scars, and other considerations. This trial aimed to evaluate and compare the surgical outcomes of two techniques—Maylard and Cherney incisions—in benign hysterectomy procedures for women. Materials and methods A randomized controlled trial was conducted in Al-Zahra Women’s Tertiary Referral University Hospital. A total of 60 patients undergoing benign hysterectomy were randomly allocated to two groups, with one group undergoing surgery with a Maylard incision and the other with a Cherney incision. Surgeries in both groups were performed by a gynecologist oncologist who was a member of the university faculty, accompanied by an Obstetrics and Gynecology Resident. Results There were no significant differences in hemoglobin levels or clinical or obstetric characteristics before surgery between the two study groups (p > 0.05). The mean time from skin incision to entering the abdominal cavity was 14.23 min for Maylard and 13.6 min for Cherney (p = 0.091). The average blood loss was 506.6 mL in the Maylard group and 429.3 mL in the Cherney group, which was statistically significant (p = 0.031). Postoperative hemoglobin levels were 11.68 g/dL in the Maylard group and 12.07 g/dL in the Cherney group (p = 0.133). Pain scores were higher in the Cherney group than in the Maylard group (p = 0.041). There were no surgical complications after 1 and 3 months in the study groups. Conclusions No complications were observed in any of the patients following the surgery. The Mylard incision showed a higher level of bleeding in comparison with the Cherney incision, which was linked to more noticeable pain. Nevertheless, both incisions are deemed as effective options for gynecological surgeries, offering superb visibility to the pelvis.